The leukocyte common antigen (CD45): a putative receptor-linked protein tyrosine phosphatase. - Charbonneau, H (1988)
A major protein tyrosine phosphatase (PTPase 1B) has been isolated in essentially homogeneous form from the soluble and particulate fractions of human placenta. Unexpectedly, partial amino acid sequences displayed no homology with the primary structures of the protein Ser/Thr phosphatases deduced from cDNA clones. However, the sequence is strikingly similar to the tandem C-terminal homologous domains of the leukocyte common antigen (CD45). A 157-residue segment of PTPase 1B displayed 40% and 33% sequence identity with corresponding regions from cytoplasmic domains I and II of human CD45. Similar degrees of identity have been observed among the catalytic domains of families of regulatory proteins such as protein kinases and cyclic nucleotide phosphodiesterases. On this basis, it is proposed that the CD45 family has protein tyrosine phosphatase activity and may represent a set of cell-surface receptors involved in signal transduction. This suggests that the repertoire of signal transduction mechanisms may include the direct control of an intracellular protein tyrosine phosphatase, offering the possibility of a regulatory balance with those protein tyrosine kinases that act at the internal surface of the membrane.